PENERAPAN ALAT PAKAN OTOMATIS BERBASIS INTERNET DAN PEMANFAANTAN MAGGOT SEBAGAI PAKAN ALTERNATIF PADA KELOMPOK PERIKANAN DI DESA PANGKALAN ACEH TAMIANG - Al Fajar, Beni; Fitria, Liza; Gustia Wibowo, Sara; Fitriani, Fitriani; muttaqin, khairul (Fakultas Teknik, Universitas Samudra, 2024)
The purpose of this service is to find alternative feed to replace commercial feed by utilizing maggot from black soldier flies (Hermetia illucens) or Black Soldier Fly (BSF) which is high in protein and the use of automatic feeding tools based on the Internet of Things (IOT) to reduce feed costs, feeding time and increase catfish production. This service was carried out for 6 months with several stages, namely the preparation stage, socialization of the PKM program, BSF fly cultivation to maggot harvesting, making IOT-based automatic feeding tools, technology application training stage, operational assistance stage, evaluation monitoring stage. Based on the results of the activity, it shows that before the implementation of the training, group members did not understand how to cultivate BSF flies. However, after the training, all group members could understand it well. Furthermore, in the activity of implementing automatic feeding equipment, the fish base group is directly involved in full so that they can operate the equipment independently later. It can be concluded that the program implementation was able to provide an understanding of BSF fly cultivation and the application of IOT-based automatic feeding devices. The implementation of the program has a positive impact, especially for the Fish Base group so that it can reduce feed costs and can control feeding appropriately so that it is more effective and efficient in accelerating the production process.